Ethnomedicine, phytochemistry, and bioactivities of Hibiscus sabdariffa L. (Malvaceae) - Narisya Idayu Mohd Suhaili; Nurhuda Manshoor (Shahrekord University of Medical Sciences, 2022)
Hibiscus sabdariffa L., belonging to the Malvaceae family, has been long used as herbal medicine, food, beverage, flavouring, and colouring agents. This study aims to review and document the evidence regarding the potential use of H. sabdariffa as ethnomedicine in some countries and its bioactive constituents and therapeutic properties. The electronic databases were used to search for the relevant information to the aims of this review up to March 2022. The high usage of H. sabdariffa as traditional medicine is due to its easy accessibility and low price. The plant is often used to treat intestinal problems, stomach disorders, and blood or liver toxicities. The plant contains phenolic compounds, including anthocyanins, flavonoids, and phenolic acids. The in vivo, in vitro, and clinical studies provide evidence that H. sabdariffa possesses therapeutic effects such as antihypertensive, antihyperlipidemic, antioxidants, antimicrobial, and antitumor activities. The studies provided scientific evidence for the statement of H. sabdariffa and its bioactive constituents in treating various diseases.